Collagen‐derived peptides modulate CD4+ T‐cell differentiation and suppress allergic responses in mice. Issue 2 (1st February 2018) - Nishikimi, Akihiko; Koyama, Yoh‐ichi; Ishihara, Sayaka; Kobayashi, Shusaku; Tometsuka, Chisa; Kusubata, Masashi; Kuwaba, Kumiko; Hayashida, Osamu; Hattori, Shunji; Katagiri, Koko
Abstract: Introduction: Collagen peptides have been widely used as a food supplement. After ingestion of collagen peptides, oligopeptides containing hydroxyproline (Hyp), which are known to have some physiological activities, are detected in peripheral blood. However, the effects of collagen‐peptide administration on immune response are unclear. In the present study, we tested the effects of collagen‐peptide ingestion on allergic response and the effects of collagen‐derived oligopeptides on CD4 + T‐cell differentiation. Methods: BALB/c mice fed a collagen‐peptide diet were immunized with ovalbumin (OVA), and their serum IgE and IgG levels, active cutaneous anaphylaxis, and cytokine secretion by splenocytes were examined. Naive CD4 + T cells were stimulated with anti‐CD3 and anti‐CD28 in the presence of collagen‐derived oligopeptides, and the expression of IFN‐γ, IL‐4, and Foxp3 was analyzed. Results: In an active anaphylaxis model, oral administration of collagen peptides suppressed serum OVA‐specific immunoglobulin E (IgE) production and diminished anaphylaxis responses. In this model, the ingestion of collagen peptides skewed the pattern of cytokine production by splenocytes toward T‐helper (Th) type 1 and regulatory T (Treg) cells. In vitro T‐helper cell differentiation assays showed that Hyp‐containing oligopeptides promoted Th1 differentiation by upregulating IFN‐γ‐induced signal transducer and activator of transcription 1 (STAT1) signaling. These oligopeptides also promoted the development of Foxp3 + Treg cells in response to antigen stimulation in the presence of TGF‐β. Conclusions: Collagen‐peptide ingestion suppresses allergic responses by skewing the balance of CD4 + T cells toward Th1 and Treg cells and seems to be a promising agent for preventing allergies and inflammatory diseases. Abstract : Collagen‐peptide feeding enhanced IFN‐γ and IL‐10 secretion by splenocytes. Mice fed a collagen peptide or control diet were immunized with OVA. Splenocytes from the immunized mice were cultured in the presence of OVA for 3 days and cytokine levels in the supernatant were measured.